Design of a digital tool for the identification of confined spaces. (May 2022) - Botti, Lucia; Mora, Cristina; Ferrari, Emilio
Abstract: Statistics on accidents in confined spaces reveal that many workers are injured and killed each year while working in confined spaces. The main cause of accidents and fatalities due to work in confined spaces is related to the lack of awareness about the presence and the risks of such unconventional workplaces. A confined space hazard assessment and risk control program should be implemented prior to access a confined space, aiming to control the risks associated with working in a confined space. This paper introduces a structured procedure and a digital tool for mobile devices, which aim to increase workers' awareness about the risks of working in confined spaces. The proposed tool investigates four different categories of confinement that characterize confined spaces: geometry, access, internal configuration, and atmosphere. After completing the procedure on the mobile application, the user, e.g. the employer or the company's safety professional, receives a list of potential issues that should be addressed before entering the space. Three case studies show the application of the proposed methodology to three suspected confined spaces. Highlights: Work in confined space is a high-risk activity causing serious and fatal accidents. Most of these accidents are due to the lack of awareness about confined space risks. This study proposes a structured procedure and a digital tool for mobile devices. The tool is a mobile application supporting the identification of confined spaces. The app provides a list of safety issues to address before entering the space.